A real-world disproportionality analysis of apalutamide: data mining of the FDA adverse event reporting system - Fang, Zhihong; Xu, Zhiqiang; Zhu, Wei; Yu, Mingming; Ji, Chunmei (Frontiers in Pharmacology, 2023)
Background: Apalutamide is a new drug class, which is approved to treat prostate cancer (PCa). The aim of our study was to assess the safety profiles of apalutamide in real-world through data mining of the US Food and Drug Administration Adverse Event Reporting System (FAERS). Method: We included adverse event (AE) reports regarding apalutamide submitted to the FAERS from 2018 quarter 1 (2018Q1) to 2022 quarter 1 (2022Q1). Disproportionality analyses, including reporting odds ratio (ROR) , were performed to to identify the signals of AEs in patients receiving apalutamide. A signal was detected if the lower limit of the 95% confidence interval (CI) of ROR >1 and at least 3 AEs were reported . Results: The FAERS database documented 4156 reports regarding apalutamide from January 1, 2018, to March 31, 2022. A total of 100 significant disproportionality preferred terms (PTs) were retained. Frequently observed AEs in patients receiving apalutamide included rash, fatigue, diarrhea, hot flush, fall,weight decreased, hypertension. The most significant system organ class (SOC) was “skin and subcutaneous tissue disorders”, which mainly consisted of dermatological adverse events (dAEs). The additional AEs observed with the significantly signal contain lichenoid keratosis, increased eosinophil count, bacterial pneumonia , pulmonary tuberculosis, hydronephrosis. Conclusion: Our findings provide valuable evidence for apalutamide safety profile in the real-world, which could help clinicians and pharmacists to enhance their vigilance and improve the safety of apalutamide in clinical practice.